1992
DOI: 10.1210/mend.6.11.1480174
|View full text |Cite
|
Sign up to set email alerts
|

Mutational removal of the major site of serine phosphorylation of the epidermal growth factor receptor causes potentiation of signal transduction: role of receptor down-regulation.

Abstract: The major site of epidermal growth factor receptor (EGF-R) serine phosphorylation is located within the COOH-terminal domain of the receptor at Ser1046/7. We have previously demonstrated that this phosphorylation site accounts for the acute desensitization of the EGF-R observed in EGF-treated cells. Here we show that the mutational removal of this negative regulatory phosphorylation site causes potentiation of signal transduction by the EGF-R. This potentiation can be accounted for in part by a block in the EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Finally, we defined a third membraneproximal domain, elimination of which resulted in a superactivating IL-10R; cells expressing these mutant IL-10R were 30-to 100-fold more sensitive to IL-10 than cells with wild-type receptor. This property of superactivation was not associated with dramatically altered ligand affinity or IL-10R number, or with detectably impaired ability to internalize ligand (in contrast to epidermal growth factor receptor [38]). We therefore suggest that this region may interact with an intracellular protein(s) which negatively regulates IL-10R activation.…”
Section: Resultsmentioning
confidence: 88%
“…Finally, we defined a third membraneproximal domain, elimination of which resulted in a superactivating IL-10R; cells expressing these mutant IL-10R were 30-to 100-fold more sensitive to IL-10 than cells with wild-type receptor. This property of superactivation was not associated with dramatically altered ligand affinity or IL-10R number, or with detectably impaired ability to internalize ligand (in contrast to epidermal growth factor receptor [38]). We therefore suggest that this region may interact with an intracellular protein(s) which negatively regulates IL-10R activation.…”
Section: Resultsmentioning
confidence: 88%
“…Besides the tyrosine phosphorylation events, EGFR can be phosphorylated at several serine and threonine residues (Bao et al, 2000;Countaway et al, 1990;Theroux et al, 1992a), which may influence the EGFR kinase activity (Countaway et al, 1992;Theroux et al, 1992b). We have recently uncovered a previously unappreciated type of EGFR phosphorylation induced by EGF stimulation in several cell types.…”
Section: Erk Activity-dependent Phosphorylation Of Egfr At Threonine-669mentioning
confidence: 99%
“…Early studies of EGFR phosphorylation at serine and threonine sites, including serine-1046, serine 1047, and threonine-654, revealed that mutations at these sites can modulate EGFR signaling and downregulation (Bao et al, 2000;Countaway et al, 1990;Countaway et al, 1992;Theroux et al, 1992a). When examining the impact of ERK-mediated EGFR phosphorylation at threonine-669 on EGFR signaling, we found that in the CHO cell reconstitution system, the mutant EGFR-T669A exhibits enhanced tyrosine phosphorylation (reflecting EGFR kinase activation) compared to wild-type EGFR upon EGF stimulation (Li et al, 2008).…”
Section: Erk Activity-dependent Phosphorylation Of Egfr At Threonine-669mentioning
confidence: 99%
“…One is the phosphorylation at Tyr1045, which provides a docking site for the ubiquitin ligase c-Cbl resulting in ubiquitination of the EGFR (18) and the others are the phosphorylation at serine or threonine residues, which are thought to represent a mechanism for attenuation of the receptor kinase activity (19,20). Among the major sites of serine and threonine phosphorylation of the EGFR, it has previously been shown that the serine 1046/1047 (Ser1046/7) phosphorylation sites are required for EGFR desensitization in EGF-treated cells (21). Moreover, mutations of Ser1046/7 are reported to cause a marked inhibition of the EGFstimulated endocytosis and desensitization of cell surface receptors (20).…”
Section: Introductionmentioning
confidence: 99%